(untitled) (Texas Journal of Medical Science, 2024)
a healthy diet is essential at any age, but in old age, it is especially important to avoid the risks associated with heart disease, diabetes, obesity and other chronic ailments. The quantity and quality of food are determined by age, sex and the nature of the work performed.The diet of the elderly differs significantly from that of the young. But a reduced calorie diet should contain a sufficient amount of mineral salts, vitamins, and proteins. The total caloric intake of the daily diet for the elderly should be reduced mainly by animal fats and simple carbohydrates.